Behavioural Characteristics and Cyberbullying Profiles among Malaysian Youngsters - Anwar R.M.; Din M.M.; Bakar A.A.; Abdul Latif A.; Rahim F.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cyberbullying is a variation of bullying that involves the use of technology to abuse others. This study examined the relationship between behavioural characteristics and cyberbullying profiles among youngsters. A total of 221 youngsters aged between 15-30 in Malaysia were surveyed, and their raw scores ran through statistical analysis. Findings show that the majority of the participants have never engaged in cyberbullying, but a few of them had experienced cyberbullying. Findings from the survey revealed that the percentages of female participants as cybervictims are higher (63.7%) than male participants (36.3%), while the percentages of male participants as bullies are higher (52.9%) than female participants (47.1%). The most prominent behaviour of cyberbullies is sending mean messages directly to cybervictims and the most prominent behaviour of cybervictims is being excluded from online groups. 2022 IEEE.